PTH-124 Endoscopic resection of early oesophageal adenocarcinoma with submucosal invasion: outcomes from a single centre. (8th June 2018) - Skouras, Thomas; Moore, Andrew; Smart, Howard
Abstract : Introduction: Endoscopic mucosal resection (EMR) for early oesophageal adenocarcinoma (EOA) is an established and accepted therapy with the outcome for cancers invading the submucosal layer (T1b) dependent upon histological risk factors of the malignancy. The aim of this study was to assess the outcomes in patients with T1b EOA in our institution. Methods: We retrospectively assessed all patients who underwent an upper GI EMR from January 2009 to December 2017 using the audit tool of UNISOFT Medical Systems – GI reporting tool (version14). We collected data regarding the histological characteristics from our ICE laboratory reporting system. Patients who were identified as having a T1b EOA were reviewed for their subsequent management and outcome using electronic hospital records and the Somerset Cancer Registry. Results: A total of 333 patients underwent 391 upper GI EMR procedures. Of these, 170 were oesophageal EMR of which 18 had EOA with submucosal invasion. All 18 were male with a mean age of 68.6 years. The EMR was en-block in 4 cases and piecemeal in the remainder. The median number of resections per procedure was 3 (IQR 1–4). The median follow up was 37 (IQR 23–56) months. No patient had complications of bleeding or perforation. Twelve of the lesions were sub-classified as SM1, 4 as SM2 and 2 as SM3. Further endoscopic and histological characteristics can be seen in table 1. Eleven patients underwent surgical resection following their initial EMR (table 2). Five are still alive, 2 died from metastatic oesophageal cancer (after 7 and 39 months respectively) and 4 died from causes unrelated to oesophageal cancer (34, 44, 58 and 67 months later). Three of the patients who underwent surgery had no residual cancer or lymph nodes found in the surgically resected specimen; one was found to have high grade dysplasia. In the remaining 7 patients not undergoing surgery, 2 were palliated and died 4 and 7 months later. The other 5 patients had either radiotherapy alone (3), chemo-radiotherapy (1) or oesophageal radiofrequency ablation (1) and are all alive to date after a median follow up of 32 (IQR 13–48) months. Conclusion: The management of patients who are found to have EOA with submucosal involvement needs to be individualised. The majority of our patients underwent further treatment. Surgical resection revealed no residual tumour in some but metastatic disease occurred in others. Treatment decisions should be taken through a multi-disciplinary approach depending upon the histological characteristics and the comorbidities of the patient.